2012
DOI: 10.1111/jop.12023
|View full text |Cite
|
Sign up to set email alerts
|

Expression of oral secretory leukocyte protease inhibitor in HIV‐infected subjects with long‐term use of antiretroviral therapy

Abstract: BACKGROUND The objectives of this study were to determine 1) expression of oral secretory leukocyte protease inhibitor (SLPI) in HIV-infected subjects compared to non-HIV controls, 2) the oral SLPI expression in HIV-infected subjects with ART compared to those without ART, and 3) factors associated with the expression of oral SLPI. METHODS Oral tissues and samples of both un-stimulated and stimulated saliva were collected from HIV-infected subjects with and without ART, and non-HIV individuals. The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The significant increase in SLPI mRNA expression and protein secretion was dose and time dependent, occurred rapidly after virus contact, did not require productive cellular infection, and was elicited specifically by the external envelope glycoproteins of HIV strains (44). A recent study by Nittayananta et al (43) reported that HIV infection may affect the expression of oral SLPI at both transcriptional and translational levels. The study showed that the expression of oral SLPI mRNA in HIV-infected individuals was increased; however, the levels of SLPI protein in stimulated saliva was decreased (43).…”
Section: What Are the Effects Of Hiv Infection On Oral Innate Immunity?mentioning
confidence: 99%
See 3 more Smart Citations
“…The significant increase in SLPI mRNA expression and protein secretion was dose and time dependent, occurred rapidly after virus contact, did not require productive cellular infection, and was elicited specifically by the external envelope glycoproteins of HIV strains (44). A recent study by Nittayananta et al (43) reported that HIV infection may affect the expression of oral SLPI at both transcriptional and translational levels. The study showed that the expression of oral SLPI mRNA in HIV-infected individuals was increased; however, the levels of SLPI protein in stimulated saliva was decreased (43).…”
Section: What Are the Effects Of Hiv Infection On Oral Innate Immunity?mentioning
confidence: 99%
“…This finding may indicate that the expression of SLPI is also controlled at the post-transcriptional level, and that HIV infection may alter message translation or interfere with the protein synthesis. In addition, the study reported that CD4 T-cell count and HIV viral load were the factors associated with the oral SLPI expression (43). Thus, HIV infection may impair the function of oral epithelial cells in innate immunity leading to the alterations of the expression of oral SLPI.…”
Section: What Are the Effects Of Hiv Infection On Oral Innate Immunity?mentioning
confidence: 99%
See 2 more Smart Citations
“…Also, it has been suggested that a form of cleaved SLPI can reflect the disease activity of patients with allergic rhinitis and asthma (Belkowski et al 2009). It was also been proposed as a biomarker in ovarian and gastric cancer (Devoogdt et al 2009;Cheng et al 2008), or to identify subjects at risk of infections and malignant transformation due to HIV infection (Nittayananta et al 2013). Recently, it was proposed as a biomarker for acute kidney injury after transplantation (Wilflingseder et al 2014).…”
Section: Biomarkermentioning
confidence: 99%